ANTIBACTERIAL AND ANTIFUNGAL ACTIVITY OF MICROWAVE ASSISTED EXTRACTION OF APPLE PEEL - HARI SHANKAR JOSHI,; ARVIND, (International Journal of Pharma and Bio Sciences, 2016)
The microwave assisted extraction (MAE) technique is emerged with great advantages over other conventional technique. Apple peel are the potential source of polyphenols, apple of Himachal variety was subjected to extract polyphenols by using microwave assisted technique and solvent extraction (SE) technique using methanol, ethanol, acetone and water as solvents. The extract obtained from the MAE showed the antimicrobial and antifungal activity against pathogenic bacteria strain named Staphylococcus aureus, E. coli and Salmonella spp. Moreover apple peel also showed the potentiality to check the growth of Fusarium verticillioides, Aspergillus niger and Penecillium spp.